2022
DOI: 10.3390/ani12131693
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Single-Step Genomic Best Linear Unbiased Prediction Method Application for Assessing Pigs on Meat Productivity and Reproduction Traits

Abstract: Changes in the accuracy of the genomic estimates obtained by the ssGBLUP and wssGBLUP methods were evaluated using different reference groups. The weighting procedure’s reasonableness of application Pwas considered to improve the accuracy of genomic predictions for meat, fattening and reproduction traits in pigs. Six reference groups were formed to assess the genomic data quantity impact on the accuracy of predicted values (groups of genotyped animals). The datasets included 62,927 records of meat and fattenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…According to the simulation results, the accuracy of genomic selection gradually increases as the number of reference populations increases. Kabanov et al used three methods to assess breeding value and predictability for five main traits of Large White pigs ( 32 ). The research results showed that the accuracy of genomic selection also gradually increases with the size of the reference population.…”
Section: Discussionmentioning
confidence: 99%
“…According to the simulation results, the accuracy of genomic selection gradually increases as the number of reference populations increases. Kabanov et al used three methods to assess breeding value and predictability for five main traits of Large White pigs ( 32 ). The research results showed that the accuracy of genomic selection also gradually increases with the size of the reference population.…”
Section: Discussionmentioning
confidence: 99%